Linking atmospheric dimethyl sulfide and the Arctic Ocean spring bloom. Issue 1 (16th January 2013) - Park, Ki‐Tae; Lee, Kitack; Yoon, Young‐Jun; Lee, Hyun‐Woo; Kim, Hyun‐Cheol; Lee, Bang‐Yong; Hermansen, Ove; Kim, Tae‐Wook; Holmén, Kim
Abstract [1] We measured atmospheric dimethyl sulfide (DMS) mixing ratios at approximately hourly intervals over a 1 year period (April 2010 to March 2011) in the Atlantic sector of the Arctic Ocean (Svalbard, Norway; 78.5°N, 11.8°E). The mixing ratios varied by several orders of magnitude over time scales of less than several days, and occasionally reached 200−300 parts per trillion by volume during the major phytoplankton growth period (May to September), whereas during the winter months (October to April) the mixing ratios were on the order of a few parts per trillion by volume. Our results, based on analyses using multiple data products (atmospheric DMS mixing ratios, satellite‐derived ocean colors, and meteorological datasets), indicated that weekly variability in the DMS mixing ratios at Svalbard was highly correlated with variability in the chl‐a concentration in waters in the vicinity of Svalbard (r = 0.89). Hourly‐to‐daily variability in the DMS mixing ratios were satisfactorily explained by changes in the trajectory, altitude, and speed of air masses passing the DMS sources prior to reaching Svalbard. The observed coupling between DMS mixing ratios and chl‐a concentration is surprising, and indicates that the variability in chl‐a concentrations in the study area represents the change in the abundance of phytoplankton capable of producing DMS. The intensive monitoring of DMS levels at Svalbard enabled us to identify in situ production and the flux of oceanic DMS over the Arctic region. It thus constitutes a useful analytical tool for detecting changes in DMS production associated with variations in phytoplankton productivity resulting from changes in sea ice extent as a consequence of Arctic seasonality and warming.